GLOBAL AND LOCAL PROCESSING WITH ORIENTATION CLASSIFICATION TASKS - Blanca Mena, María José; Luna, Rafaela; López- Montiel, Dolores; Rando Calvo, Belén; Zalabardo, Caridad (Anales de Psicología / Annals of Psychology, 2001)
Recently, it has been suggested that the task is an important determinant of global dominance. Blanca, Luna, López, Zalabardo & Rando (in press) found a global advantage with an orientation classification task and neither a global nor local advantage with a target detection task. The aim of this experiment is to find out whether the results found with orientation classification tasks are replicated using hierarchical stimuli with a less number of local elements. If the requirement of the task is an important factor, then the reduction in the number of local elements should not have an effect and global advantage should be appeared. In the experiment, participants are instructed to indicate the direction (left/right) of the opening of a semicircle in both divided and selective attention conditions, while the exposure duration was varied (ilimited or 150 msec.) The results demonstrated a global advantage in the two attention conditions, which was independent on the exposure duration, supporting the idea of global dominance in orientation classification tasks.